Implementing COVID-19 (SARS-CoV-2) Rapid Diagnostic Tests in Sub-Saharan Africa: A Review - Jacobs, Jan; Kühne, Vera; Lunguya, Octavie; Affolabi, Dissou; Hardy, Liselotte; Vandenberg, Olivier (Frontiers in Medicine, 2020)
Background: In response to the COVID-19 (SARS-CoV-2) pandemic, the World Health Organization called for point-of-care diagnostics. COVID-19 antigen-detection Rapid Diagnostic Tests (COVID-19 Ag RDTs) are attractive to expand diagnostics in sub-Saharan Africa (sSA). Objectives: To reflect on product- and healthcare-related requirements for implementation of COVID-19 Ag RDTs in sSA. The COVID-19 Ag Respi-Strip (Coris BioConcept) was used as a benchmark. Content: COVID-19 Ag RDT product-related challenges comprise specimen type (nasopharyngeal (flocked) swabs), sample stability and appropriateness for subsequent molecular testing. The sensitivity of the benchmark product is too low to use as a stand-alone test for triage, cluster investigation and surveillance. The strip-in-tube format is not user-friendly; single packs including flocked swabs should be considered. Instructions for use should be adapted to the end-user's literacy and anticipated errors. Apart from diagnostic accuracy, studies in sSA should assess operational characteristics (test line intensity, migration, invalid results, anomalies) and environmental challenges. Implementation monitoring can detect low-prevalence reasons of test failure and end-user errors. Integration in sSA healthcare settings requires a target product profile, landscape overview of technologies, manufacturing capacity, a sustainable market and a stringent but timely regulation. In-country deployment depends on integration in the national laboratory network coordinated by the National Reference Laboratory which overviews selection, distribution, quality control, implementation, supervision, communication and post-market surveillance. Harmonization is key. Valuable experience is available from disease-specific programs such as malaria. Implications: The present perspective reveals challenges and opportunities for the design and implementation of COVID-19 Ag RDTs tailored to the context of sSA.